Proporsi Tepung Beras Merah dan Tepung Kedelai terhadap Kualitas Wingko - Utama, Dio Alif; Puspitasari, Diana; Rejeki, Fungki Sri (Program Studi Teknologi Pangan, 2020)
Wingko is a traditional food that has potenstial to be developed. Diversification of wingko can be done by using brown rice flour and soybean flour, which also expected to increase the nutritional content of wingko. The research objective 1). To determine the effect of the proportion of glutinous rice flour, brown rice flour, and soybean flour on the quality of wingko, 2) To determine the financial feasibility of wingko. This research used factorial randomized block design. Factor 1 is brown rice flour and factor 2 is soybean flour. The parameters tested were moisture, ash, crude fiber, protein, and organoleptic tests which included aroma, taste, color, and texture, as well rancidity (physical), and microbial tests (visually). Selection of alternatives using the expectation value methods. Financial feasibility parameters include BEP (Break Even Point), NPM (Net Present Value), IRR (Internal Rate of Return), and PP (Payback Period).The result showed that B2K1 treatment was selected with total expectation value 7.66. This treatment has a yield percentage 9.75%, 13.48% moisture content, 1.96% ash, 6.45% protein, 7.50% crude fiber, 34.60% aroma parameters, 45.60% taste, 40.00% texture, and 13.30% color. The results of financial analysis with parameters of BEP, NPV, IRR,and PP can be concluded that wingko production business design is feasible to be developed